Effect of socio-economic, demographic and environmental factors on nutritional status of elderly: a cross sectional study - Patil, Darshan J.; Shindhe, Maheshkumar M. (International Journal Of Community Medicine And Public Health, 2019)
Background: Worldwide elderly population is rapidly increasing. This is posing many challenges in elderly population. Malnutrition in them is one of the major problems but ignored component. Socio-economic, demographic and environmental factors are those greatly influence their nutritional status. Hence the present study was undertaken to assess the effect of socio-economic, demographic and environmental factors on nutritional status of elderly. Methods: The present study was a cross-sectional study which included 545 elderly population of Uchagaon subcentre and was carried out over a period of 1½ years. After selecting Uchagaon subcentre by simple random sampling technique and house to house survey was carried out to select eligible elderly participants who met the selection criteria. Data was collected from eligible elderly by using pretested questionnaire and Mini Nutritional Assessment (MNA) tool. Results: 65.1% were between the age group of 60-69 years. 55% were females, 66% were currently married, 60% had no formal schooling, 67.2% were belongs to socio-economic status of either class IV/V. 23.5% were malnourished and 49% were at risk of malnutrition. There was association found between nutritional status of elderly with increase in age, marital status, educational status, occupation, socio-economic status, type of family and housing condition. Conclusions: In the present study majority of the elderly were at risk of malnutrition. The nutritional status of elderly was associated with increase in age, marital status, educational status, occupation, socio-economic status, type of family and housing condition of rural elderly and subsequently modify those factors to improve the nutritional status of elderly and this can be a scope for further study in future.